2011
DOI: 10.1002/anie.201100104
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Chain Polymeric Nanoparticles by Stepwise Folding

Abstract: Light‐induced self‐assembly leads to the folding of synthetic random‐coil polymers into highly stable single‐chain polymeric chiral nanoparticles (see picture; green: side chains, blue: phenyl rings, red: nitrophenyl leaving groups). The folding of the polymer was aided by heating and cooling steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 56 publications
8
179
1
1
Order By: Relevance
“…31,[34][35][36][37][38] These results suggest that the controlled topology of the polymer chains allows the selfassembly motifs, that is, BTA units and Ru(II)-SDP units, to act in an orthogonal way. 27,34 Dynamic light scattering (DLS) experiments were performed to elucidate the single chain folding of the prepared copolymers. When linear polymers fold into SCPNs, hydrodynamic diameters (D H ) of around 10 nm are expected.…”
Section: CD Dls and Fluorescence Characterization Of P1-p5 In Solutionmentioning
confidence: 91%
“…31,[34][35][36][37][38] These results suggest that the controlled topology of the polymer chains allows the selfassembly motifs, that is, BTA units and Ru(II)-SDP units, to act in an orthogonal way. 27,34 Dynamic light scattering (DLS) experiments were performed to elucidate the single chain folding of the prepared copolymers. When linear polymers fold into SCPNs, hydrodynamic diameters (D H ) of around 10 nm are expected.…”
Section: CD Dls and Fluorescence Characterization Of P1-p5 In Solutionmentioning
confidence: 91%
“…For the systems in which folding is governed by BTA self-assembly, CD spectroscopy is a powerfull technique as shown by Mes et al (28). When the BTAs are non-racemic, helical aggregates of one helicity are biased and this assembly process gives rise to a signature Cotton effect.…”
Section: Characterization Of Dynamic Scpnsmentioning
confidence: 96%
“…The size of the SCPNs could be tuned via varying the molecular weight of the polymer (37). Foillowing these first experiments, Mes et al showed that benzene-1,3,5-tricarboxamides (BTAs) can also be utilized as a supramolecular unit to form SCPNs (28). In this example, a prepolymer was synthesized via activators regenerated by electron transfer atom transfer radical polymerization (ARGET-ATRP), using isobornyl methacrylate and silyl-protected propargyl methacrylate as the monomers.…”
Section: Synthetic Access To Dynamic Scpnsmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to these advances that stem from a thorough understanding of the polymerization mechanisms involved, more and more complex polymeric structures have been synthesized, such as brush polymers, 10,11 dendrimers, [12][13][14] micrometer-sized toroids, 15 and polymers that fold and unfold in a controlled fashion. [16][17][18][19] Concomitant to the development of polymeric structures formed by covalent bonds, supramolecular polymers have been introduced. [20][21][22][23] In these structures, the building blocks of the polymer are connected by noncovalent interactions like hydrophobic interactions, hydrogen-bonding, and metal-ligand bonding.…”
mentioning
confidence: 99%